FILLING THE EDUCATIONAL SPACE OF PERSONAL STUDENT PERSONALITY DEVELOPMENT DURING THE PERIOD OF ADAPTATION TO SCHOOL LIFE (SYSTEM OF DEVELOPMENTAL DEVELOPMENT) (Pedagogy of Higher and Secondary Education, 2022)
The article describes process of creation and filling the subsystem of educational space such as "teacher-child-parents" in the adaptionall period of child's entrance to a school life of system of developing training.
Keywords: 1